2022
DOI: 10.33394/jpu.v3i2.5305
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Perangkat Pembelajaran Abad 21 Berbasis Merdeka Belajar bagi Guru di Kabupaten Indragiri Hulu Riau

Abstract: This service activity aims to provide training on learning tools for teachers in Indragiri Hulu Regency, Riau. The service method used the form of discussions and practices, while the steps for implementing the service were; 1) the stage of preparation and development of training materials; 2) the training stage; 3) the stage of assistance in making learning devices. The results of this service indicated that the training could improve teachers' ability to make learning tools, namely RPP, Media, Teaching Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…(Nellitawati et al, 2022) revealed that training and direct technical assistance were needed regarding how to prepare teaching tools by bringing in experts who are experts in the field of Independent Curriculum teaching tools. As stated by several researchers and writers, teacher abilities and competencies can be improved through training (Mulyawan, 2012)(Sa'bani, 2017 (Rukayah, 2018) (Supentri, Jumili Arianto, Ahmal, Yuliantoro, 2020) explains that the training carried out can improve the competence and ability of teachers in developing learning tools based on independent learning. The stages are 1) the stage of preparation and development of training materials, 2) the stage of training, and 3) the stage of assisting in the preparation of learning tools.…”
Section: Discussionmentioning
confidence: 99%
“…(Nellitawati et al, 2022) revealed that training and direct technical assistance were needed regarding how to prepare teaching tools by bringing in experts who are experts in the field of Independent Curriculum teaching tools. As stated by several researchers and writers, teacher abilities and competencies can be improved through training (Mulyawan, 2012)(Sa'bani, 2017 (Rukayah, 2018) (Supentri, Jumili Arianto, Ahmal, Yuliantoro, 2020) explains that the training carried out can improve the competence and ability of teachers in developing learning tools based on independent learning. The stages are 1) the stage of preparation and development of training materials, 2) the stage of training, and 3) the stage of assisting in the preparation of learning tools.…”
Section: Discussionmentioning
confidence: 99%
“…Meskipun demikian kategori sedang terjadi sebab masih ada peserta didik menyukai pelajaran fisika, yang beranggapan bahwa pelajaran fisika merupakan ilmu terapan yang berguna dalam kehidupan sehari-hari, motivasi belajar ini membuat peserta didik tersebut tertarik dan berusaha untuk mempelajari fisika dan juga fisika tidak hanya belajar teori melainkan melaksanakan praktikum atau percobaan. Hal ini sejalan dengan penelitian tentang minat dan motivasi peserta didik di era pembelajaran abad 21 (Nirmayani & Dewi, 2021;Supentri et al, 2022) tentang perlunya model dan media pembelajaran untuk meningkatkan motivasi dan hasil belajar siswa.…”
Section: Gambar 5 Diagram Batang Kemampuanunclassified